2000
DOI: 10.1086/313992
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Host- and Variety-Dependent Characteristics of Infection Due to Cryptococcus neoformans in Australia and New Zealand

Abstract: A prospective population-based study was conducted in Australia and New Zealand during 1994-1997 to elucidate the epidemiology of cryptococcosis due to Cryptococcus neoformans var. neoformans (CNVN) and C. neoformans var. gattii (CNVG) and to relate clinical manifestations to host immune status and cryptococcal variety. The mean annual incidence per 10(6) population was 6.6 in Australia and 2.2 in New Zealand. Of 312 episodes, CNVN caused 265 (85%; 98% of the episodes in immunocompromised hosts) and CNVG cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
362
4
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(404 citation statements)
references
References 24 publications
26
362
4
12
Order By: Relevance
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009). This divergence in results may be due to a possible lack of uniformity in the methodologies of testing adopted by different investigators.…”
Section: Discussionsupporting
confidence: 88%
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009). This divergence in results may be due to a possible lack of uniformity in the methodologies of testing adopted by different investigators.…”
Section: Discussionsupporting
confidence: 88%
“…The need for recognition of the two species within C. neoformans is warranted not only because of their biologic and ecological differences, but also because they tend to infect different hosts. C. gattii infections have been documented more commonly in immunocompetent individuals, whereas a majority of the patients infected with C. neoformans are immunocompromised, often due to HIV infection [10,11]. Furthermore, some reports have suggested that infections due to C. gattii carry a worse prognosis [12].…”
Section: Classification Of Cryptococcus Neoformans and C Gattiimentioning
confidence: 99%
“…This incidence is significantly greater than that of C. gattii infection typically observed in Australia (0.94 cases per million residents per year), where C. gattii is endemic (3,6). A public advisory was issued by the British Columbia Centre for Disease Control on June 6, 2002 (www.bccdc.org) advising the public, medical practitioners, and veterinarians of the potential health risk and telling them to be alert for symptoms and to seek early diagnosis.…”
mentioning
confidence: 99%